2018
DOI: 10.1136/bmjopen-2017-020348
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of seat belt use behaviour: a protocol for a systematic review

Abstract: IntroductionThe use of seat belts could prevent severe collision damage to people in vehicle accidents and keep passengers safe from sustaining serious injuries; for instance, it could prevent passengers from being thrown out of a vehicle after the collision. The current systematic review will identify and analyse the determinants of seat belt use behaviour.Methods and analysisWe will include qualitative, quantitative and mixed methods studies reporting the acquired data from passengers aged more than 12 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…As for the second objective of the study, we found that, although several similarities can be observed across male and female teenagers, some key differences are noticeable. Accordingly, previous studies on road safety behaviour have shown that, even though great similarities and uniform patterns may be observed across genders, key differences in the role of demographic factors, mental health and educational aspects might explain differential outcomes in both risky and protective road behaviours of individuals 30–32. Also, several studies have already suggested that risky road behaviours can be more frequent and dangerous, and protective behaviours less prevalent in the case of male road users 1 18 32…”
Section: Discussionmentioning
confidence: 99%
“…As for the second objective of the study, we found that, although several similarities can be observed across male and female teenagers, some key differences are noticeable. Accordingly, previous studies on road safety behaviour have shown that, even though great similarities and uniform patterns may be observed across genders, key differences in the role of demographic factors, mental health and educational aspects might explain differential outcomes in both risky and protective road behaviours of individuals 30–32. Also, several studies have already suggested that risky road behaviours can be more frequent and dangerous, and protective behaviours less prevalent in the case of male road users 1 18 32…”
Section: Discussionmentioning
confidence: 99%
“…According to Word Health Organization’s previous reporting, the African region has the highest traffic injury death rates, while the European region has the lowest [ 2 ]. Other studies have also highlighted that the prevalence of seat belt use is not high in low- and middle-income countries, and more than 90% of the world’s road fatalities occur in these countries [ 7 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of seat belt use varies across different countries of the world and depends to some extent on the regulations in place. Seat belt use in low- and middle-income countries is not high, despite strict driving laws and fines for those who do not use seat belts [ 6 , 7 ]. Studies have shown that men, young people (18–34 years old), obese individuals, rear seat occupants, and villagers have lower rates of seat belt use [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%